2022
DOI: 10.3389/fpsyt.2022.891325
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Self-rating Depression Scores and Total Ghrelin and Adipokine Serum Levels in a Large Population-Based Sample

Abstract: BackgroundGhrelin and the adipokines leptin and adiponectin have been suggested to be involved in mood and anxiety regulation and to be altered in affective disorders. However, studies investigating the association between ghrelin, leptin and adiponectin and depressive symptomatology are scarce but might contribute to a better understanding of their involvement in mood regulation. We thus aimed investigating the association between depressive symptomatology and total ghrelin as well as leptin and adiponectin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Concerning depressed mood, some studies in patients with MDD have reported correlations between ghrelin levels and depressive symptoms (Algul andOzcelik, 2018, Akter et al, 2014), while other studies found that ghrelin infusions are associated with an improved depressed mood (Kluge et al, 2011). Notwithstanding, other studies observed no association (Kluge et al, 2009, van Andel et al, 2022, Wittekind et al, 2022, adding to the mixed set of interim results. Crucially, most studies did not differentiate between the two isoforms of ghrelin, acyl, and des-acyl ghrelin, which may contribute to the variability in their findings.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning depressed mood, some studies in patients with MDD have reported correlations between ghrelin levels and depressive symptoms (Algul andOzcelik, 2018, Akter et al, 2014), while other studies found that ghrelin infusions are associated with an improved depressed mood (Kluge et al, 2011). Notwithstanding, other studies observed no association (Kluge et al, 2009, van Andel et al, 2022, Wittekind et al, 2022, adding to the mixed set of interim results. Crucially, most studies did not differentiate between the two isoforms of ghrelin, acyl, and des-acyl ghrelin, which may contribute to the variability in their findings.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism is unclear, but it is hypothesized that both inherent sex differences, mediated by X-chromosomal effects and neuroanatomical differences (70) as well as protective effects of 17β-estrogen play a key role in this phenomenon (71). Interestingly, this effect is not only present in appetite regulation and energy homeostasis but has been observed in MDD and/or depressive symptomatology as well (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…They did not observe any significant difference in regard to ghrelin concentration between depressed and non-depressed subjects. Also, there was no association between CES-D scores and total ghrelin levels ( 51 ). It should be noted that the diagnosis of depression was not confirmed by a psychiatrist nor any standardized clinical interview.…”
Section: Relationship Between Ghrelin Concentration and Major Depress...mentioning
confidence: 99%